The comparison of deciduous teeth eruption pattern in small gestational age (SGA) and appropriate gestational age (AGA) children - Kirana, Irawati; Oewen, Roosje Rosita; Soewondo, Williyanti (Padjadjaran Journal of Dentistry, 2010)
Introduction: Small Gestational Age (SGA) children is defined as infant whose birth’s weight was below the tenth percentile intrauterine growth and development curve of Lubchenco. There are two types of SGA children, namely symmetrycal SGA (the disturbance occurred in the first trimester of pregnancy) and asymmetrical SGA (the disturbance occured in second and third trimesters of pregnancy). The aim of this research was to obtain the deciduous teeth eruption patterns in symmetrical and asymmetrical of SGA children, based on baby teeth that  have erupted the eruption of primary teeth. Methods: The research design was descriptive and analytical, with cross-sectional design and using the given sample size. The sample were 28 SGA children aged 1-4 years and 33 Appropriate Gestational Age (AGA) children. Determination of SGA children based on Ponderal Index. Eruptive stage was determined by Nola Modification Scoring by the score between 0-4. (Score (0) for tooth that have not erupted; (1) tooth emerge, (2) ⅓ crown  erupted tooth, (3) ½ crown erupted tooth, (4) full crown tooth. Results: The results showed, that there were differences in the pattern of deciduous teeth eruption based on teeth eruption stages that have been erupted. Eruption pattern of SGA children deciduous teeth were slower than the eruption pattern of AGA children deciduous teeth. Conclusion: Different patterns of deciduous teeth eruption in symmetrical SGA children and asymmetrical SGA children were showed. Viewed from the stand point of view the stage of teeth eruption, the deciduous teeth eruption pattern of symmetrical SGA children was slower than the asymmetrical SGA children.